Awareness toward bankruptcy risk among employees of MAA Takaful Berhad, Jalan Ipoh, Kuala Lumpur / Muhamad Azraei Idros and Nurhanisah Abdullah - Idros, Muhamad Azraei; Abdullah, Nurhanisah (Faculty of Business and Management, 2013)
The research reported in this paper is the basic research on “Awareness Toward Bankruptcy Risk Among Employees of MAA Takaful Berhad, Jalan Ipoh, Kuala Lumpur”. Nowadays, bankruptcy is one of the leading factors that contribute people to be affected with financial risk. Increasing in Credit Card Debts, Medical Bills and Insurance fee can cause more expenses instead of saving. Here, the awareness toward factors influencing bankruptcy risk is very important. The main objective of this research are (1) to determine the level of awareness among employees of MAA Takaful toward bankruptcy risk, (2) To examine the relationship between literacy, experience and attitude with the awareness toward bankruptcy risk and (3) To determine most influential factor that contributes to the awareness of bankruptcy risk. 186 questionnaires were distributed to employees of MAA Takaful Berhad, Jalan Ipoh, Kuala Lumpur. The researcher applied a convenience sampling as the sampling technique. Throughout this research, the level awareness is recorded as in a high level group of awareness with 4.6210 amount of mean. Generally, there are moderate and significant relationship between independent variable (literacy, experience and attitude) and dependent variable (awareness). The most influential factor is experience with coefficient of 0.552. This coefficient shows that for every unit increase in experience, a 0.552 unit increase in the level of awareness toward factors influencing bankruptcy risk among employees of MAA Takaful. The result shows a positive relationship between experience and awareness toward bankruptcy risk among employees of MAA Takaful. In conclusion, several recommendations had been come out by researchers in order to improve the research at certain field.